Ecological Water Quality Water Treatment and Reuse - Voudouris, Kostas (IntechOpen, 2012)
This book attempts to cover various issues of water quality in the fields of Hydroecology and Hydrobiology and present various Water Treatment Technologies. Sustainable choices of water use that prevent water quality problems aiming at the protection of available water resources and the enhancement of the aquatic ecosystems should be our main target.